Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s00268-021-06404-w
|View full text |Cite
|
Sign up to set email alerts
|

P‐POSSUM and the NELA Score Overpredict Mortality for Laparoscopic Emergency Bowel Surgery: An Analysis of the NELA Database

Abstract: Background Risk stratification has become a key part of the care processes for patients having emergency bowel surgery. This study aimed to determine if operative approach influences risk‐model performance, and risk‐adjusted mortality rates in the United Kingdom. Methods A prospectively planned analysis was conducted using National Emergency Laparotomy Audit (NELA) data from December 2013 to November 2018. The risk‐models investigated were P‐POSSUM and the NELA Score, with model performance assessed in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…P‐POSSUM had a similar c‐statistic to SORT (0.796) but overpredicted mortality; this was consistent with previous reports. This can be explained by the fact the model was developed around 20 years ago when surgical mortality was higher [23, 26]. P‐POSSUM had much better discrimination in the study by Wong et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P‐POSSUM had a similar c‐statistic to SORT (0.796) but overpredicted mortality; this was consistent with previous reports. This can be explained by the fact the model was developed around 20 years ago when surgical mortality was higher [23, 26]. P‐POSSUM had much better discrimination in the study by Wong et al.…”
Section: Discussionmentioning
confidence: 99%
“…This could therefore reduce PRE‐OP accuracy in data on exclusively open surgery. However, a recently published analysis of national NELA data has found that P‐POSSUM and the NELA score consistently overpredict mortality for laparoscopic surgery [26]. Thus, it may be of benefit that PRE‐OP has been developed on a more even mix of operative approaches, allowing it to provide a more balanced, if slightly less accurate, prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The risks associated with emergency laparotomy, such as wound and secondary infections, long-term morbidity and mortality are widely recognised [13]. The elderly and frail represent a patient cohort with reduced physiological reserve, impairing their ability to tolerate the intense burden of emergency laparotomy; as a result, the likelihood and severity of adverse outcomes is significantly increased [7].…”
Section: Discussionmentioning
confidence: 99%
“…These clinical composite scoring systems utilise descriptive parameters such as baseline functional status and co-morbidities to generate a numerical output of risk expressed as a percentage [4][5][6]. These techniques require a comprehensive clinical history which may not be available in the emergency setting and are subjective in nature, risking the under-or over-estimation of morbidity and mortality in certain patient groups [7].…”
Section: Ofmentioning
confidence: 99%
“…It was also shown that patients and clinicians had different views on what defined a positive outcome after emergency laparotomy. Current pre-operative scoring and risk stratification systems for emergency laparotomy such as the National Emergency Laparotomy Audit (NELA) score or Portsmouth Physiological and Operative Severity Score for the 2 numeration of Mortality and morbidity (P-POSSUM) do not take into account or provide prediction tools for post-operative QoL [ 5 ].…”
Section: Introductionmentioning
confidence: 99%